Pengaruh Atribut Produk, Harga Dan Store Image Terhadap Keputusan Pembelian Sate Klatak Di Kabupaten Bantul, Yogyakarta (Studi Kasus Warung Sate Klatak Pak Bari) - Dika Utama, Syahrul; Kusumastuti, Anie Eka (Jurnal Ekonomi Pertanian dan Agribisnis, 2024)
The study aims to determine consumers profile of klatak satay as well as the effect of product attribute, price, and store image towards purchasing decision of klatak satay at Mr. Bari's Klatak Satay Stall. The study was conducted Mr. Bari's Klatak Satay Stall, Wonokromo Market, Jalan Imogiri Timur number 5, Pleret, Bantul, Yogyakarta from November to December 2022. The research sample chosen by purposive sampling as much as 100 respondent. Data collected by direct observation, interviews using structured questionnaires, and documentation. Data then analyzed by using descriptive analysis, validity test, reliability test, factor analysis, classic assumption test, multiple regression analysis, and hypothesis testing. The results showed the characteristics of consumers who purchase Mr. Bari's Klatak Satay Stall dominated by male age ranging of 18-28 years old with education level graduated form bachelor degree and work as self-employed have an average income >IDR 5.000.000/month with the origin of domicile outside the Province of Yogyakarta and mostly got information about Mr. Bari's Klatak Satay Stall from recommendations from friends, relatives or family. It can be concluded that product attribute variables and store image variables affect the purchasing decision of klatak satay at Mr. Bari's Klatak Satay Stall, while the price variable did not affect the purchasing decision of klatak satay at Mr. Bari's Klatak Satay Stall. The most influential variable on the purchasing decision of klatak satay at Mr. Bari's Klatak Satay Stall is the store image variable